2017
DOI: 10.2974/kmj.67.87
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Diabetes Mellitus in Locally Advanced Non-small Cell Lung Cancer

Abstract: Background: To investigate the prognostic significance of patient characteristics and clinical laboratory test results in locally advanced non-small cell lung cancer (NSCLC), and in particular the impact of diabetes mellitus (DM) on the survival of patients who underwent chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…Type 1 DM (T1DM) and type 2 (T2DM) were not differentiated in these publications. Four studies were from Asia [17][18][19][20] and 13 were from western countries. [21][22][23][24][25][26][27][28][29][30][31][32][33] Most studies were published within the last 10 years and the sample sizes ranged from 146 to 10378.…”
Section: Study Description and Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 1 DM (T1DM) and type 2 (T2DM) were not differentiated in these publications. Four studies were from Asia [17][18][19][20] and 13 were from western countries. [21][22][23][24][25][26][27][28][29][30][31][32][33] Most studies were published within the last 10 years and the sample sizes ranged from 146 to 10378.…”
Section: Study Description and Quality Assessmentmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30][31][32][33] Most studies were published within the last 10 years and the sample sizes ranged from 146 to 10378. Seven of the studies 17,19,24,25,27,29,31) investigated the outcomes of patients undergoing surgical treatment, while six studies 18,21,23,26,30,33) focused on those receiving non-surgical treatments like chemotherapy or radiotherapy and three studies 20,22,32) recruited patients receiving both of them. All but one study were retrospective cohort studies while the only exception was designed as a prospective cohort.…”
Section: Study Description and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature reports that diabetes mellitus has a significant impact on the prognosis of gastric cancer, colorectal cancer, breast cancer and other malignant tumors . However, there are few studies on the impact of diabetes mellitus on lung cancer, and there are differences in their findings . At present, most of the studies on lung cancer with diabetes mellitus are on patients with advanced disease who are receiving chemoradiotherapy, while there are relatively few studies on patients with lung cancer and diabetes mellitus undergoing surgery in the early and middle stages .…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes is regarded to be associated with an increased risk of lung cancer [84], despite several conflicting retrospective studies on lung cancer prognosis among diabetic patients [85,86]. On the basis of two large cohorts from Shanghai, it was reported that the risk of lung cancer was observed in both men and women, with a HR of 0.87 and 0.92, respectively [87].…”
Section: Epidemiologymentioning
confidence: 99%